Penggunaan Strength untuk Meningkatkan Engagement dan Kinerja Karyawan - Pundani Eki Pratiwi; Gusti Yuli Asih; Dewi Puspita Sari (Faculty of Psychology, Universitas Semarang, 2021)
AbstractThis study aims to determine the effect of strength use on employee engagement and performance. This study uses a quantitative explanatory research approach, with 173 subjects of credit division at BPR Restu Group Central Java and DIY. Processing data in this study using the SPSS 20.00 program for windows by looking at the descriptive test and path analysis. There are three hypotheses proposed in the study and the results of the analysis show that H1, H2, and H3 can be accepted. The analysis results show that the value of Sig.F 0.000 <0.05 for the three hypotheses. The contribution of the influence of strength use (X) to engagement (Y1) is 14.1%. Strength use (X) and engagement (Y1) also affect employee performance (Y2) by 37.2%. The results also indicate an indirect effect of strength use (X) on performance (Y2) through employee engagement (Y1). The more employees are able to use their strengths, the more engagement they have and indirectly will increase the employee s performance.Keywords: Engagement, Explanatory Research, Performance, and Strength Use